DISCOVERY OF CONSTRUCTIVE ABILITIES OF VERBS (VERB VALENCY) IN SERBIAN LANGUAGE TEACHING - methodical application - Милица М. Савић (Faculty of Philosophy, University of Novi Sad, City Library of Pančevo, 2011)
In this paper the insight is given on how the valency of verbs, as their constructive ability to attach certain number of terms in a sentence to themselves is included in the teaching of Serbian language. With a short overview of the relevant methodical and expert literature, the specific method model is given in order to show how pupils can independently reveal the different sentence structures and models by using textbooks and semi-programmed instructions. The elaborated methodical application, based on contemporary methodical systems, forses pupils to actively participate in teaching-learning process and it leads to their discovery of structuring the sentence with less difficulty, according to their own learnig pace.